Using Modern Conservation Tools for Innovative Management of Coral Reefs: The MANACO Consortium - Selmoni, Oliver; Lecellier, Gaël; Ainley, Lara; Collin, Antoine; Doucet, Raimana; Dubousquet, Vaimiti; Feremaito, Hudson; Ito Waia, Edouard; Kininmonth, Stuart; Magalon, Hélène; Malimali, Siola’a; Maugateau, Ateliana; et al. (Frontiers in Marine Science, 2020)
Coral reefs are under threat and innovative management strategies are urgently required. However, discoveries from innovative fields of coral reef research are rarely transposed in practical conservation actions. This is mainly due to the difficulties in knowledge exchange between scientists and conservation stakeholders. The ManaCo consortium (http://manaco.ird.nc/) is an international network federating conservation stakeholders and researchers in a common effort to preserve the coral reefs. The focus is on using modern tools to build a bridge between indigenous knowledge and scientific innovation. ManaCo aims to orientate research towards relevant conservation needs and to facilitate the transposition of research into concrete management strategies. This will allow to coordinate a collaborative response against coral reef decline. We invite anyone sharing the same interests in joining us.